A post-phenomenological analysis of using menstruation tracking apps for the management of premenstrual syndrome. (December 2022) - Riley, Sarah; Paskova, Klara
Objectives: Menstruation tracking digital applications (MTA) are a popular technology, yet there is a lacuna of research on how women use this technology for the management of PMS. Theoretical frameworks for understanding users' experiences are also underdeveloped in this nascent field. The objectives of the study were therefore twofold, to propose a theoretical framework for understanding women's use of MTA and apply it to the analysis of users' experiences in the management of PMS. Method: A novel theoretical framework was proposed, informed by post-phenomenology, postfeminist healthism, feminist new materialism and digital health technologies as public pedagogy. This framework focuses analytic attention on affective relationships between subjectivity, bodily sensations, digital technology, and discourse. It was used to structure the analysis of five in-depth timeline interviews with women in Aotearoa New Zealand who experienced benefits from using MTA to manage PMS symptoms. Results: Three pedagogical relationships were identified: a pedagogy of empowerment, where users learnt to control, predict and manage their PMS symptoms in line with healthism; a pedagogy of appreciation, where users learnt to understand their menstruating bodies as amazing, a valued part of them, and awe-inspiring that radically overturned past internalised stigma; and an 'untrustworthy teacher' who eroded this affirmative learning through inaccuracy, positioning users in dis-preferred categories, or being 'creepy'. Conclusions: MTA offers huge possibilities for challenging menstrual stigma that need to be nurtured, developed, and protected; and there are benefits for analysing MTA within wider scholarship on postfeminist healthism.